Compared to What? Is BMI Associated with Histopathological Changes in Laparoscopic Sleeve Gastrectomy Specimens? - Tamer Saafan (14151819) (2019)
Obesity is a risk for many different cancers. Laparoscopic sleeve gastrectomy (LSG) is common, and benign or pre-malignant histopathology types are reported in the removed gastric specimens. We assessed whether higher BMI was associated with certain benign or pre-malignant histopathological changes. Retrospective chart review of all primary LSG patients (N = 1555). Demographic, clinical, and LSG histopathology data were retrieved. BMI of patients with specific benign or pre-malignant conditions in their gastric specimens was compared with the BMI of the rest of the patients with abnormal histopathology specimens and also compared with the BMI of patients with normal control specimens. Females comprised 70% of the patients. Mean BMI were 46.3 (females) and 48 (males). Normal LSG specimens comprised 52%. Most common abnormal histopathologies were chronic inactive gastritis (33%), chronic active gastritis (6.8%), follicular gastritis (2.7%), lymphoid aggregates (2.2%), intestinal metaplasia (1.4%) and GIST (0.7%). After controlling for confounders (age, gender, H. pylori, diabetes mellitus type 2, hypertension), no significant association was observed between the BMI of patients with specific benign or pre-malignant histopathology compared with the BMI of the rest of the patients with abnormal histopathologies and compared to the BMI of patients with normal histopathologies. When confounders were taken into account, there appeared no significant associations between the BMI of patients with specific benign or pre-malignant histopathology compared with the BMI of the rest of the patients with abnormal histopathologies and compared to the BMI of patients with normal histopathologies of their gastric specimens. There was a very weak correlation between BMI and other covariates. Other Information Published in: Obesity Surgery License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11695-019-03801-y